Penafsiran Surah Al-Raḥmān Ayat 1–4 dan Implementasinya dalam Nilai-Nilai Pendidikan Islam di Yayasan Duta Inspirasi Al-Quran Deli Serdang - Qurrata Aini; Amroeni Drajat; Juli Julaiha P. (Yayasan Albahriah Jamiah Indonesia, 2026)
The integration of the interpretation of Surah al-Raḥmān verses 1–4 into Islamic educational practices is crucial in building a value-oriented epistemological foundation, but there is still a gap between normative textual interpretation and pedagogical implementation in educational institutions. This study aims to analyze the construction of verse interpretation, identify the interpretation of educational values ​​by institutional actors, and explore their implementation in educational practices at the Al-Quran Inspiration Ambassador Foundation in Deli Serdang. A qualitative approach is used through interpretation studies and case studies with data collection techniques in the form of in-depth interviews, participant observation, and documentation, which are then analyzed thematically and comparatively between the views of classical and contemporary exegetes and institutional practices. The results show that the interpretation construction emphasizes the dimension of mercy as the basis of educational relations, taʻlīm as a systematic process of knowledge transmission, and bayān as the ability to articulate and critical literacy. The interpretation by teachers and administrators shows the internalization of values ​​contextually through an integrative curriculum, dialogic learning strategies, and the habituation of communicative ethics. The implementation of these values ​​is manifested in a compassion-based learning design, strengthening Quranic literacy competencies, and developing students’ expressive abilities, despite challenges such as limited pedagogical resources, variability in educators’ understanding, and inconsistent evaluations. The implications of this study include strengthening interpretation as the epistemological basis of Islamic education and formulating an adaptive and contextual implementation model of Quranic values ​​in educational institutions.